Strength and durability status of the Fagfog Quarzite from the Lower Nawakot Group, central Nepal Lesser Himalaya - Sharma, Dinesh Raj; Tamrakar, Naresh Kazi (Journal of Nepal Geological Society, 2023)
Railways have played vital role in the development of many countries worldwide. Government of Nepal has already planned to establish various national and international railway networks within the nation. A substantial quantity of durable rock ballasts is required for building a sustainable railway network. Quartzites from central Nepal Lesser Himalaya can be a promising source to fulfill this requirement. Therefore, the quartzites from the stratigraphic unit Fagfog Quartzites of the Lower Nawakot Group located in Dhading District along the Kalu Pandey Highway have been assessed to determine physical, strength and durability characteristics of the ballasts. All quartzite ballasts obtained from the bedrocks were of Precambrian, medium-grained, bladed to prolate shaped, white to brownish white, crushed quartzites. Dry density and water absorption were respectively 2336-2641 kg/m3 and 0-2.5%. The bulk density varies from 1204 and 1387 kg/m3. Point load strength index varies from 2.04 to 11.55 MPa (medium strong to extremely strong). Aggregate Impact Value (AIV) and Aggregate Crushing Value (ACV) ranges from 14.85 to 22.77% and 15.51 to 22.17% respectively. Some 7% results of AIV and 20% of ACV results exceeded the established limiting value of 22%. The slake durability index (Id5) ranges from 95.19 and 99.11%, whereas Id2 ranged between 96.94 and 100%, which shows that 80% of the samples have very high slake durability whereas remaining 20% exhibit high slake durability. There was no significant change in slake durability index from the second to the fifth cycles. Los Angeles Abrasion Value (LAAV) varies from 12.07 to 31.34% and Sulphate Soundness Value (SSV) varies within a limited range of 0.20 and 4.59%. Conclusively, the comprehensive evaluation suggests that the quartzite ballast from the Fagfog Quartzite source display favourable qualities in terms of point load, crushing and impact strengths and durable against abrasion, slaking and frosting. Thus, the quartzites from Fagfog Quartzite hold significant potential as a suitable rock type for railway track ballasts.